2005
DOI: 10.1097/01.ede.0000152524.89074.bf
|View full text |Cite
|
Sign up to set email alerts
|

Size at Birth and Gestational Age as Predictors of Adult Height and Weight

Abstract: Birth length is perhaps a better predictor of adult height and weight than birth weight, and should be considered as a possible risk factor for adult morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
102
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 20 publications
10
102
0
2
Order By: Relevance
“…In girls and boys birth length and BMC were significantly positive associated in crude models. Interestingly, a study by Eide et al [32] aimed to examine the contribution of birth length and birth weight on adult length and weight. They suggested that birth length perhaps is a better predictor of adult height and weight than birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In girls and boys birth length and BMC were significantly positive associated in crude models. Interestingly, a study by Eide et al [32] aimed to examine the contribution of birth length and birth weight on adult length and weight. They suggested that birth length perhaps is a better predictor of adult height and weight than birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that birth weight measurements are more reliable than length measurements [41] and that birth length measurements show less variability when compared with birth weight measurements. Thus, it has been discussed whether this variable should be treated as a discrete variable, even when measured and reported as cm [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lifelong morbidities among survivors include cerebral palsy, intellectual impairment, chronic lung disease and vision and hearing loss (3). Increased blood pressure, accelerated weight gain and growth failure are also among the comorbidities (2,12,13). In this review, we will highlight current information on growth in children born prematurely, mainly referring to publications with preterm classification based on GA; the hormonal abnormalities possible associated with lack of catch-up growth after the first months of life and discuss the potential treatment with recombinant human growth hormone (rhGH) for those who remain with short stature during infancy and childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, body measurements at birth have been made with the emphasis on referencing birth body length to population standards and are now approached more often as a screening tool used for children with an ele-www. journals.viamedica.pl/ginekologia_polska vated risk of growth disturbances and non-communicable diseases (NCDs) [12][13][14]. Therefore, formulation of specific recommendations for further care for neonates and children in their first months and years of life, especially, careful monitoring of growth and avoiding overfeeding, depends on the adequate and accurate body measurements at birth.…”
Section: Introductionmentioning
confidence: 99%